The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1186/s12885-019-5724-z
|View full text |Cite
|
Sign up to set email alerts
|

High level of circulating vitamin D during neoadjuvant therapy may lower risk of metastatic progression in high-risk rectal cancer

Abstract: Background Following curative-intent neoadjuvant therapy in locally advanced rectal cancer, metastatic progression is still dominant. We investigated if patients’ circulating 25-hydroxyvitamin D [25(OH)D] levels were associated with outcome. Methods Serum 25(OH)D concentration was assessed by liquid chromatography-mass spectrometry in samples collected from 84 patients at baseline, completion of the neoadjuvant therapy, and treatment evaluation before surgery, and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…The highly similar effect of calcitriol on colon tumor and rectal tumor organoids is consistent with the finding that colon and rectal cancers, excluding hypermutated cancers, have similar patterns of genetic alterations [ 65 ]. Moreover, our finding also agrees with the proposed protective effect of vitamin D on both colon and rectal cancers [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The highly similar effect of calcitriol on colon tumor and rectal tumor organoids is consistent with the finding that colon and rectal cancers, excluding hypermutated cancers, have similar patterns of genetic alterations [ 65 ]. Moreover, our finding also agrees with the proposed protective effect of vitamin D on both colon and rectal cancers [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The gut physiology is profoundly affected by the action of vitamin D [ 17 ], and observational studies have established a link between vitamin D deficiency and an elevated risk and poor prognosis of CRC, suggesting that colon and rectal cancer patients might preferentially benefit from an adequate vitamin D status [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Data from recent interventional clinical studies indicate that the addition of vitamin D to standard chemotherapy improves the progression-free survival of metastatic CRC patients [ 29 ]; however, another randomized trial showed no preventive effect on adenoma recurrence [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antitumour effect of vitamin D is a popular research topic. Epidemiological studies have compared the relationship between serum vitamin D levels and prognosis in patients with breast cancer 25 and rectal cancer 26 and have found that the higher the serum level of vitamin D is, the better is patient prognosis. The regulatory relationship between vitamin D and tumours has not yet been elucidated, and its mechanism has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been an increasing number of studies investigating the effect of 25-OH vitamin D on progression-free survival and overall survival in patients with colorectal cancer (24)(25)(26). It has been also revealed that infective complications are increased in hospitalized patients with vitamin D de ciency because of its decreased immunomodulatory effects (27,28).…”
Section: Discussionmentioning
confidence: 99%